At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve this problem, we will first expand the left-hand side of the given equation [tex]\((a x+2)(b x+3)\)[/tex] and then match the coefficients with the right-hand side [tex]\(15 x^2 + c x + 6\)[/tex].
Let's start by expanding [tex]\((a x + 2)(b x + 3)\)[/tex]:
[tex]\[ (a x + 2)(b x + 3) = (a x)(b x) + (a x)(3) + (2)(b x) + (2)(3) \][/tex]
[tex]\[ = ab x^2 + 3a x + 2b x + 6 \][/tex]
Combine the like terms [tex]\(3a x + 2b x\)[/tex]:
[tex]\[ = ab x^2 + (3a + 2b) x + 6 \][/tex]
Now, we want this to be equal to [tex]\(15 x^2 + c x + 6\)[/tex] for all values of [tex]\(x\)[/tex]. Therefore, we can equate the coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term from both sides of the equation.
By comparing coefficients we get:
[tex]\[ ab = 15 \][/tex]
[tex]\[ 3a + 2b = c \][/tex]
[tex]\[ 6 = 6 \][/tex]
The last equation (constant term) is always true and doesn't provide us any new information. We are left with:
1. [tex]\(ab = 15\)[/tex]
2. [tex]\(3a + 2b = c\)[/tex]
3. [tex]\(a + b = 8\)[/tex]
We need to find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy both [tex]\(ab = 15\)[/tex] and [tex]\(a + b = 8\)[/tex].
Consider the quadratic equation whose roots are [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ t^2 - (a + b)t + ab = 0 \][/tex]
Substitute [tex]\(a + b = 8\)[/tex] and [tex]\(ab = 15\)[/tex]:
[tex]\[ t^2 - 8t + 15 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula [tex]\(t = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A}\)[/tex]:
[tex]\[ t = \frac{8 \pm \sqrt{64 - 60}}{2} \][/tex]
[tex]\[ t = \frac{8 \pm \sqrt{4}}{2} \][/tex]
[tex]\[ t = \frac{8 \pm 2}{2} \][/tex]
[tex]\[ t = \frac{8 + 2}{2} = 5 \quad \text{or} \quad t = \frac{8 - 2}{2} = 3 \][/tex]
So, the possible values for [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are 5 and 3, respectively.
Now, substitute these values back into [tex]\(3a + 2b = c\)[/tex]:
1. If [tex]\(a = 5\)[/tex] and [tex]\(b = 3\)[/tex]:
[tex]\[ c = 3(5) + 2(3) = 15 + 6 = 21 \][/tex]
2. If [tex]\(a = 3\)[/tex] and [tex]\(b = 5\)[/tex]:
[tex]\[ c = 3(3) + 2(5) = 9 + 10 = 19 \][/tex]
Therefore, the two possible values for [tex]\(c\)[/tex] are 19 and 21.
So, the correct answer is:
[tex]\[ \boxed{(C) 19, 21} \][/tex]
Let's start by expanding [tex]\((a x + 2)(b x + 3)\)[/tex]:
[tex]\[ (a x + 2)(b x + 3) = (a x)(b x) + (a x)(3) + (2)(b x) + (2)(3) \][/tex]
[tex]\[ = ab x^2 + 3a x + 2b x + 6 \][/tex]
Combine the like terms [tex]\(3a x + 2b x\)[/tex]:
[tex]\[ = ab x^2 + (3a + 2b) x + 6 \][/tex]
Now, we want this to be equal to [tex]\(15 x^2 + c x + 6\)[/tex] for all values of [tex]\(x\)[/tex]. Therefore, we can equate the coefficients of [tex]\(x^2\)[/tex], [tex]\(x\)[/tex], and the constant term from both sides of the equation.
By comparing coefficients we get:
[tex]\[ ab = 15 \][/tex]
[tex]\[ 3a + 2b = c \][/tex]
[tex]\[ 6 = 6 \][/tex]
The last equation (constant term) is always true and doesn't provide us any new information. We are left with:
1. [tex]\(ab = 15\)[/tex]
2. [tex]\(3a + 2b = c\)[/tex]
3. [tex]\(a + b = 8\)[/tex]
We need to find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy both [tex]\(ab = 15\)[/tex] and [tex]\(a + b = 8\)[/tex].
Consider the quadratic equation whose roots are [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ t^2 - (a + b)t + ab = 0 \][/tex]
Substitute [tex]\(a + b = 8\)[/tex] and [tex]\(ab = 15\)[/tex]:
[tex]\[ t^2 - 8t + 15 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula [tex]\(t = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A}\)[/tex]:
[tex]\[ t = \frac{8 \pm \sqrt{64 - 60}}{2} \][/tex]
[tex]\[ t = \frac{8 \pm \sqrt{4}}{2} \][/tex]
[tex]\[ t = \frac{8 \pm 2}{2} \][/tex]
[tex]\[ t = \frac{8 + 2}{2} = 5 \quad \text{or} \quad t = \frac{8 - 2}{2} = 3 \][/tex]
So, the possible values for [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are 5 and 3, respectively.
Now, substitute these values back into [tex]\(3a + 2b = c\)[/tex]:
1. If [tex]\(a = 5\)[/tex] and [tex]\(b = 3\)[/tex]:
[tex]\[ c = 3(5) + 2(3) = 15 + 6 = 21 \][/tex]
2. If [tex]\(a = 3\)[/tex] and [tex]\(b = 5\)[/tex]:
[tex]\[ c = 3(3) + 2(5) = 9 + 10 = 19 \][/tex]
Therefore, the two possible values for [tex]\(c\)[/tex] are 19 and 21.
So, the correct answer is:
[tex]\[ \boxed{(C) 19, 21} \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.